2014
DOI: 10.1159/000360079
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Twin Anemia/Polycythemia Sequence by Syngeneic Partial Exchange Transfusion

Abstract: Twin anemia/polycythemia sequence (TAPS) is characterized by large intertwin hemoglobin (Hb) differences without signs of twin oligopolyhydramnios. The spontaneous form complicates approximately 3-5% of monochorionic twin pregnancies. TAPS placentas are characterized by the presence of only very few and small unidirectional arteriovenous anastomoses, which allow a slow transfusion of blood from the donor to the recipient, gradually leading to highly discordant Hb levels. Neonatal morbidity in TAPS appears to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Since TAPS twins share their blood circulation and therefore have exactly the same blood cell characteristics, it may be of additional value to transfuse the anemic twin with the recipient's whole blood as a donor source instead of foreign donor blood. Recently, Yarci et al (2014) reported a case of TAPS in which the anemic donor was successfully transfused after delivery with blood obtained from the polycythemic co-twin during PET. The main advantage of this new therapeutic method is avoidance of donor exposure and of the risk of blood product infections (Yarci et al, 2014).…”
Section: Intrauterine Blood Transfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since TAPS twins share their blood circulation and therefore have exactly the same blood cell characteristics, it may be of additional value to transfuse the anemic twin with the recipient's whole blood as a donor source instead of foreign donor blood. Recently, Yarci et al (2014) reported a case of TAPS in which the anemic donor was successfully transfused after delivery with blood obtained from the polycythemic co-twin during PET. The main advantage of this new therapeutic method is avoidance of donor exposure and of the risk of blood product infections (Yarci et al, 2014).…”
Section: Intrauterine Blood Transfusionmentioning
confidence: 99%
“…Recently, Yarci et al (2014) reported a case of TAPS in which the anemic donor was successfully transfused after delivery with blood obtained from the polycythemic co-twin during PET. The main advantage of this new therapeutic method is avoidance of donor exposure and of the risk of blood product infections (Yarci et al, 2014). Whether this new approach may lead to decreased morbidity in TAPS pregnancies requires further investigation.…”
Section: Intrauterine Blood Transfusionmentioning
confidence: 99%
“…This condition occurs in approximately 5% of MCDA pregnancies spontaneously. It is seen even more frequently (12%) after fetoscopic laser treatment for TTTS [75][76][77][78][79][80] Poor neurodevelopmental outcomes including isolated cognitive delay, motor delay and cerebral palsy rates range greatly be- 86 tween 2 and 20% in both the donor and recipient twins who are affected by TAPS [81] .…”
Section: Morbiditymentioning
confidence: 99%
“…The search identified 265 articles, of which 122 were assessed with respect to their eligibility for inclusion and 40 were included in the systematic review 8,16,23–25,28–62 (Table 1, Figure S1). Thirty‐eight studies reported outcomes according to the type of TAPS in 502 pregnancies (306 (61.0%) with spontaneous TAPS and 196 (39.0%) with postlaser TAPS) and 21 studies reported outcomes according to management in 417 pregnancies with TAPS diagnosed prenatally.…”
Section: Resultsmentioning
confidence: 99%